Inspirations from Outside (R&E-SOURCE, 2014)
As a regular reader of journals, daily and weekly newspapers, digital newsletters, etc, I got many inspirations for treating the presented problems or ideas by means of a CAS. It is obvious that tables presented in scientific and economic journals inspire for graphic representation and statistic investigations. This will not be treated in this talk.My examples shall demonstrate that one can find interesting and challenging problems for applying a CAS not only in textbooks. These problems can be for students of various mathematical levels and just for one’s own entertainment. Among these examples are: modelling a baroque pillar with an interesting cross section, finding an analytic proof for a geometric problem, investigating the equation of a locus which was generated by a dynamic geometry program, modelling a special evolution strategy, and modelling the pricing of call & put options. Solving brain twisters discovered in journals or in respective collections of such problems with a CAS need other competencies than solving them by reasoning (see also my respective workshop).A very special inspiration was given by working with LUA – a programming language which can be used with TI-NspireCAS. Clifford Pickover’s “Mygalomorphs” get a new quality by applying sliders for changing shape and colours rapidly. This realisation of the “inspiration” was the result of a fruitful communication with a Swiss colleague.In my demonstration I will use mainly DERIVE and TI-NspireCAS – because I am most familiar with these both systems.